Sharḥ Nahj al-balāghah - Baḥrānī, Maytham ibn ʻAlī, d. 1280? (Daftar Nashr al-Kitāb, 1983)
Commentary on Nahj al-balāghah, writings and sermons of ʻAlī ibn Abī Ṭālib, Caliph, 600 (ca.)-661; Shiite interpretation.